CLINICOPATHOLOGICAL FEATURES OF 322 CASES OF CYSTIC LESIONS OF THE JAWS: A RETROSPECTIVE ANALYSIS - Amos Schwartz (International Journal of Medical Science and Public Health Research, 2024)
Cystic lesions of the jaws are a diverse group of pathologies that can present a wide range of clinical, radiological, and histopathological features. These lesions are commonly encountered in clinical practice, and accurate diagnosis is crucial for determining the appropriate management strategies. This study presents a clinicopathological analysis of 322 cases of cystic lesions of the jaws, aiming to identify the most prevalent types, their clinical presentation, and histopathological characteristics. Data were retrospectively collected from patient records, including clinical examination findings, radiographic images, histological reports, and treatment outcomes. The most common cystic lesions observed were odontogenic cysts, with the dentigerous cyst and the keratocystic odontogenic tumor being the most frequently diagnosed subtypes. A significant portion of cases also involved non-odontogenic cysts such as the nasopalatine duct cyst and the traumatic bone cyst. Radiographically, the majority of cysts appeared as well-defined, expansile lesions, often associated with impacted teeth. Histological examination revealed varying degrees of epithelial lining changes, including squamous, columnar, or odontogenic epithelium, which were essential in differentiating the cystic types. The management of these lesions ranged from conservative surgical approaches to more aggressive resection in cases of recurrent or malignant potential. The findings of this study are supported by a review of current literature, highlighting advances in diagnostic techniques, including imaging modalities and molecular studies, which have improved the understanding and treatment outcomes of these lesions. This comprehensive study provides valuable insights into the clinical and pathological features of jaw cysts, emphasizing the importance of accurate diagnosis for optimal management.